New interaction paradigms to fight the digital divide : a pilot case study regarding multi-touch technology - Carvalho, Diana (2012)
Information and Communication Technologies (ICTs) are considered a powerful tool for economic development and the growth of societies. However, instead of helping overcome society's inequalities caused by the digital era, the have instigated an increase of the people that rested aside of the information age. The digital divide refers to the difficulty infoexcluded people have in keeping up with technological advances. This phenomenon was triggered by the rapid growth and dissemination of technological equipment, as a portion of society did not have the proper time or knowledge to adjust. This paper sets forth a new approach to help fight the Portuguese digital divide by presenting new ways of interaction. Resorting to multi-touch technology, we examine how this new natural interaction paradigm can have a positive influence in the struggle against info-exclusion. For this purpose, we present a multi-touch game envisioned to encourage and teach digitally excluded people on how to use an important and needed everyday equipment the ATM (Automated Teller Machine) as it is still avoided by some. We believe that our pilot case study can show preliminary results on how natural user interfaces may be beneficial to help overcome some difficulties enforced by the digital divide. We consider that our findings may be valuable to show a possible path of how the new natural user interfaces can help bring technology and people closer. After being asked about their user experience, the participants of this exploratory study agreed that the game encouraged them to explore more about new technologies